2005
DOI: 10.1080/014850190953294
|View full text |Cite
|
Sign up to set email alerts
|

The Only Presence of Sperm in Urine Does Not Imply Retrograde Ejaculation

Abstract: & This is a retrospective study of clinical experience collected at the University Clinical Hospital over a 19-year period. Semen samples were analyzed according to WHO criteria. In the postmasturbatory urine, sperm count was performed. Data were expressed as total sperm number in urine (TSNU) and using a retroejaculation index. Patients were categorized into four groups according to the presence of sperm in the studied samples: a) in semen and urine; b) only in urine; c) only in semen; d) neither in semen nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…What differentiates the present study from former examinations of sperm in PEU [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] is that the time intervals between ejaculation and the first micturition were preset. At the first sampling, we instructed our volunteers to wait for 30 min after ejaculating for their first micturition, for 2 h at the second, and for 4 h at the third micturition.…”
Section: Participants and Proceduresmentioning
confidence: 64%
See 1 more Smart Citation
“…What differentiates the present study from former examinations of sperm in PEU [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] is that the time intervals between ejaculation and the first micturition were preset. At the first sampling, we instructed our volunteers to wait for 30 min after ejaculating for their first micturition, for 2 h at the second, and for 4 h at the third micturition.…”
Section: Participants and Proceduresmentioning
confidence: 64%
“…Many investigations that followed concluded that the evaluation of spermaturia can be very useful to determine gonadal maturation [5][6][7][8][9]. The fact that spermatozoa can be found in the post-ejaculatory urine (PEU) in infertile as well as fertile grown-up men was confirmed in several reports [10][11][12][13][14][15]. The result has become a hope for patients with retrograde ejaculation.…”
Section: Introductionmentioning
confidence: 92%
“…Sperm in the urine can be due to retrograde ejaculation, or due to the expulsion of urethral sperm during voiding. 26 Various cut-offs for PEU sperm count have been used to define retrograde ejaculation, but there is no clear consensus and very little data on the subject. One method is to establish a threshold urine sperm count above which retrograde ejaculation is diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…In urine collected after ejaculation (PEU), at least one sperm was observed in 60 to 88% of fertile or fecund men [8, 12, 13] and in 65 to 98% of infertile men depending on the study [8, 11, 13, 14]. The most plausible explanation is that sperm remaining in the urethra after ejaculation are washed out in the PEU [1113].…”
Section: Introductionmentioning
confidence: 99%
“…However, taken alone, the only presence of sperm in the PEU does not indicate PRE [14]. The use of a retro-ejaculatory index (R-ratio), which expresses the total number of sperm recovered in PEU as a percentage of the total number of sperm found in both semen and PEU, has been suggested to define PRE [8, 13, 14].…”
Section: Introductionmentioning
confidence: 99%